Pengaruh Seni Asitektur Terhadap Perkembangan Pendidikan Islam di Andalusia - Nurul Hidayati; Yazida Ichsan; Ratna Wulandari; Dwi Aknan Lutfiyan (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
The discourse related to the influence of architecture on the development of Islamic education in Andalusia is actually a very important discussion to do. On the one hand, from a historical perspective, under the Umayyah II dynasty, Andalusia became a beacon of civilization in the fields of science, technology and art that contributed to Europe. On the other hand, art as part of the manifestation of civilization is rarely studied, especially its influence on Islamic education. The purpose of this research is to know and describe how the development of architectural arts and its effects on Islamic education. The purpose of this research is to identify and describe how the development of architectural arts and its effects on Islamic education. This research is a historical research which is carried out in several steps: heuristics, criticism, interpretation and historiography. The results showed that the triumph of Islam in Andalusia left a special space in the representation of Western civilization even today. Various historical relics have had their own influence on culture and culture in Spain, especially Islamic architectural arts. Mosques, palaces, forts, tombs, and secular buildings in Spain are heavily influenced by Islamic culture. Apart from being a legacy of Islamic culture, the art of architecture in Andalusia has a strong influence on the development of Islamic education in modern-day Spain. Especially in the development of Islamic education, architectural art has a strategic position in its influence. This can be seen in the calligraphic patterns in mosques and other important places in Andalusia that use pieces of the Al-Qur'an verses as their motifs. This verse piece is not only an ornament but aims to introduce Islam to the community and as proof that Islam had an influence in Andalusia.